PENERAPAN SISTEM PENGENDALIAN MANAJEMEN UNTUK MENINGKATKAN MOTIVASI KERJA MARKETING - Renny Darsono; Adhicipta Raharja Wirawan (CALYPTRA, 2018)
Abstract- Human resources were the most important elements to determine whether the company strategy was successful or not. How well the system was built, the aspect of human beings in the company needed to get special attention so that it didn’t cause chaos for the company. Management Control System could help companies to develope and manage the action of employees so that the purpose of the company could be achieved. In this research,the researcher investigated the Management Control System which had been implemented by PT. Tirto Agung Abadi Motor. This study was aimed to examine the control system and the support factors, in order to increase staff marketing motivation company. This research would be conducted with a qualitative approach in the applied method research. The company was known having marketing with low motivation, it was caused by the existence of Management Control System in the company that couldn’t give enough motivation on itsemployees.In addition, this thesis was aimed to give recommendations about kind of Management Control System that could be used to increase the marketing motivation with training-based employees so that it could fulfill the target in order to achieve the aim of the company itself,either by changing, adding, or removing company regulations that had been determined before.